Bacteriological Spectrum and Sensitivity Pattern in Culture Proven Urinary Tract Infection in Children - Mulazim Hussain , Nasira Bhatti ,Bilal Ahmad,Shagufta Husain, Mulazim Hussain , Nasira Bhatti ,Bilal Ahmad,Shagufta Husain (Journal of Rawalpindi Medical College, 2017)
To determine the different types of organisms causing urinary tract infections in children and their sensitivity to antibiotics. Methods: This cross sectional study was conducted at Children Hospital, PIMS Islamabad and consisted of 117 patients of either gender between age of 03 months to 12 years. Results: Mean age of children enrolled in our study was 4.4 (± 2.6) years. Out of 117 patients, 63 (54 %) were girls. The most common isolate was E. coli (57.3%) percent, followed by Klebsiella (18.8 %), Staphylococcus aureus (13.7 %), Pseudomonas (5.1 %) and Proteus (3.4 %) children. All isolates were sensitive to ciprofloxacin, of loxacin, amikacin, cefixime and imepenem. Only 38.5% E coli and 37.5% Klebsiella were sensitive to Ampicillin, and 14.3% E coli and 9.1% Klebsiella were sensitive to Trimethoprim-sulphamethoxazole. Conclusion: The most common isolate was E. coli, followed by Klebsiella, Staphylococcus aureus, Pseudomonas and Proteus. Most antibiotics tested for the E. coli, Klebsiella, Staphylococcus, Pseudomonas and Proteus are effective except Cotrimoxazole, Ampicillin, and Gentamicin which show high resistance